Internal urethral stent (Lasheen urethral stent) for hypospadias repair - Ahmed E Lasheen (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Background: Hypospadias is a relatively common congenital defect of the male external genitalia. There is much controversy about using of the urethral stent with hypospadias repair. Our study offers new urethral stent (Lasheen urethral stent) to facilitate repair procedure, more comfortable, and improve outcome. Methods: Twenty seven penile hypospadias cases were subjected to tabularized incised plate (TIP) repair at Zagazig University Hospital, from the period April 2017 to April 2018. Special type of urethral stent which formed of two parts; fi rst one is hard part (piece of ordinary urinary catheter) about 2 cm in length, its diameter 8 or 10 French , and fi xed from outside one suture at distal end with long two limbs of Prolene No. 3/0.